THE EFFECT OF MOTHER-TO-BABY SKIN CONTACT ON DECREASING FEVER AFTER DPT1/HB1/HIB1 IMMUNIZATION IN THE WORK AREA OF THE BANCAK HEALTH CENTER, SEMARANG REGENCY - Tri Murti, Warih Handayani; Widyastuti, Erna; Rahayu, Sri (Journal of Applied Health Management and Technology, 2021)
One of the immunizations included in the government program is DPT immunization. The side effect of DPT immunization is high fever which can be treated such as giving antipyretic drugs, increasing breast milk, and wiping or in warm water compresses (IDAI, 2011). The purpose of this study was to prove the effect of mother-to-child skin contact on reducing fever after DPT1/Hb1/Hib1 immunization in the Bancak Health Center, Semarang Regency. This research method uses a Quasi Experimental design with a Pretest-Posttest Non Equivalent Control Group Design. The population of this study was the number of infants who were immunized by DPT1/Hb1/Hib1 in the Work Area of the Bancak Health Center, Semarang Regency, as many as 63 babies. The technique used in this research is non-probability sampling with purposive sampling type. The results showed that there was a significant difference in the average decrease in body temperature of infants with fever after DPT1/Hb1/Hib1 immunization in the intervention group and the control group (p-value 0.001). It is hoped that families, health workers and the community can apply skin to skin in handling baby fever.